Introduction to graphics communications for engineers - Bertoline, Gary R. (McGraw-Hill Higher Education, 2006)
Introduction to Graphics Communication for Engineers is a short introductory technical drawing text intended for use in technical drawing or drafting courses at two and four year schools or other technology programs. Powerful computers and CAD software are of little use to engineers who do not fully understand the fundamentals of graphics communication principles and 3-D modeling strategies, or do not possess a level of visualization ability. Because of this, Bertoline concentrates on the concepts and skills necessary to sketch and create 2-D drawings and 3-D CAD models in this text. New to the third edition are "Design in Industry Boxes" that cover an aspect of design as practiced in industry. Quotes and interesting stories from practicing engineers make the boxes motivating and informative for students. Also new are practice sketching problems included throughout each chapter, which allow students a chance to practice what they are learning. This book is part of the B.E.S.T. (Basic Engineering Series and Tools), which consists of modularized textbooks offering virtually every topic and specialty likely to be of interest to engineers.